Element Extraction in Packaging Design of Cireng Rujak X with Kansei Engineering Method - Sari, Novi Purnama; Indriany, Dita Febrian; Yunisyah, Fadilah; Wiguna, Nada Nabilla (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2025)
Frozen Cireng Rujak is popular for its practicality, but the packaging of Cireng Rujak X still has many shortcomings that affect its quality. These issues arise from packaging that cannot be resealed and labels that are easily damaged. This research aims to determine the elements and design outcomes of Cireng Rujak X packaging based on consumer preferences. The study employs the Kansei Engineering method to understand consumer perceptions of the packaging. This method is supported by Quantification Theory Type-1 (QTT-1) to identify design elements. The selected concept based on QTT-1 is